Bimbingan Teknis Pengelolaan Keuangan Desa Berbasis Aplikasi Siskeudes Versi 2.0.6 Dan Pembinaan Hukum Terkait Implementasi UU No. 3 Tahun 2024 Di Provinsi Bengkulu - Saputra, Harius Eko (Jurnal Dehasen Untuk Negeri, 2023)
This technical guidance program aimed to enhance the capacity of village officials in managing village finances using the Siskeudes Version 2.0.6 application, as well as understanding the legal aspects of implementing Law No. 3 of 2024. Identified issues include limited technological skills among village officials, insufficient understanding of updated regulations, and the risk of legal violations in village fund management. The activity was held for three days at Hotel Mercure Bengkulu and involved participants from 50 villages. The training method included lectures, direct simulations, and pre- and post-test evaluations. Results showed a 32% increase in participants’ understanding, with 90% expressing satisfaction. This program proved effective in promoting more accountable and transparent village financial governance and strengthening inter-village networking. Future initiatives should include follow-up training and online discussion forums to ensure continued application of the knowledge gained.